a: \(=4\left(x^2-\dfrac{5}{2}x+\dfrac{1011}{2}\right)\)
\(=4\left(x^2-2\cdot x\cdot\dfrac{5}{4}+\dfrac{25}{16}-\dfrac{8063}{16}\right)\)
\(=4\left(x-\dfrac{5}{4}\right)^2-\dfrac{8063}{4}>=\dfrac{08063}{4}\)
Dấu '=' xảy ra khi x=5/4
b: \(=3\left(x^2-\dfrac{5}{3}x+\dfrac{1}{3}\right)\)
\(=3\left(x^2-2\cdot x\cdot\dfrac{5}{6}+\dfrac{25}{36}-\dfrac{13}{36}\right)\)
\(=3\left(x-\dfrac{5}{6}\right)^2-\dfrac{13}{12}>=-\dfrac{13}{12}\)
Dấu '=' xảy ra khi x=5/6
d: \(\left(x+2\right)^2+2\left|x+2\right|+3\ge3\)
Dấu '=' xảy ra khi x=-2